«Hours of Intense Fraternity»: Cultural journals, political projects, and Chilean-Peruvian solidarity (1920-1932) - Ugarte, Emilio José (2025)
This article analyzes the cultural magazines of the 1920s and early 1930s as a space for interaction and convergence between young progressive Chileans and Peruvians. These publications were a product of the University Reform and Chilean-Peruvian tensions and became centers of camaraderie, discussion and circulation of ideas, which would be transformed in the following years into political action and solidarity. The case of the Peruvian APRA exiles supported by Chilean socialists represents one of the most important and intense moments of collaboration in the bilateral history of the two countries.